2016
DOI: 10.2528/pierc16102801
|View full text |Cite
|
Sign up to set email alerts
|

CSRR Inspired Conductor Backed CPW-Fed Monopole Antenna for Multiband Operation

Abstract: Abstract-A conductor backed coplanar waveguide (CPW) fed multiband antenna inspired by CSRR MTM is presented. The shorting of ground in CPW feed and conductor backed arrangement extend the area of ground plane. The proposed antenna consists of rectangular monopole with Complementary Split Ring Resonator (CSRR) engraved in the extended ground plane. The prototype antenna is designed, fabricated and measured. CSRR characteristics are also analyzed. Simulated and measured results of the antenna are in good agreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In order to facilitate multiband operation, a microstrip patch in the form of a rectangle loaded with Complementary Split-Ring Resonators (CSRR) and fed from the left offset was developed [18]. For operating on all three bands, it was suggested that a CSRR-filled conductor-backed CPW antenna be used [19]. Different techniques of designing a multiband antenna have been discussed in [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In order to facilitate multiband operation, a microstrip patch in the form of a rectangle loaded with Complementary Split-Ring Resonators (CSRR) and fed from the left offset was developed [18]. For operating on all three bands, it was suggested that a CSRR-filled conductor-backed CPW antenna be used [19]. Different techniques of designing a multiband antenna have been discussed in [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…He introduced a band gap to control the stimulated and spontaneous emission of light [7]. These materials have interesting physical properties (in terms of propagation) for electromagnetic waves in both the optical and microwave fields, but more particularly in the fields of antenna [8][9][10][11][12][13][14]. There have already been several different antennas suggested for use in 5G communication applications.…”
Section: Introductionmentioning
confidence: 99%
“…The different techniques used to obtain multi-band antennas are: metamaterial structure [5,6], fractal technology [7 -13] loading stubs [14,15] and etching slots [16,17]. There are various designs of multi-band antennas in the literature.…”
Section: Introductionmentioning
confidence: 99%